Fast-tracked to prosperity or into poverty? an assessment of Zimbabwe’s fast-track resettlement programme on beneficiaries’ lives at Beacon Kop farm in Shurugwi District - Matsa, Mark (Clarion University of Pennsyslavia, 2016)
Beneficiaries of Zimbabwe’s Fast Track Land Resettlement Programme (FTLRP) have been admired by fellow citizens who for different reasons failed to access land under this accelerated national agrarian reform programme which started in July 2000. With the land being the backbone of the peasant economy which characterizes Zimbabwe’s rural areas, it was every peasant farmer’s wish to own virgin land or land in the country’s prime farming regions and move from the generally exhausted poor soils of the communal areas. Of course most communal farmers who needed land got it but have their lives improved as a result or they are now worse off? This study sought to assess Zimbabwe’s FTLRP on beneficiaries’ lives at Beacon Kop farm in Shurugwi ward 17. Questionnaires, informal group discussions as well as participatory observations were used to solicit data from the randomly selected respondents both from the villagized plots (ordinary beneficiaries) and the war veterans’ plots. Results show that the beneficiary farmers indeed needed land. Their zeal to produce was however stifled by many factors which included unavailability and inadequacy of inputs (including drought power) as well as the erratic and unpredictable climatic regime characterized by extremities like floods and droughts. Basic social services and infrastructure like boreholes, clinics, schools and roads are either unavailable or too far off to be of significant help to them. Many concede that their villages of origin were much better in terms of services delivery than their new home area but are hopeful for a better future. The study recommends that the government make available both seed and fertilizers well before the start of the planting season so that farmers can plan ahead with confidence. The government must also provide loans for early tillage programmes payable after good harvests. The government must also drill boreholes, organize farmers into cooperatives, and encourage them to produce horticultural products for sale to the nearby city of Gweru which has a ready market. A Primary school and a Secondary school as well as a clinic must also be built in order to improve the lives of the resettled farmers and their families. Government cannot achieve all this on its own. It is therefore important that it convinces the international community that the FTLRP is a foregone historical process which must be supported for the benefit of beneficiaries and the country’s development at large.